Ekspresi Spiritualitas Kelompok Keagamaan di Beberapa Wilayah Provinsi Aceh - Hanif Saputra (Jurnal Sosiologi Agama Indonesia, 2023)
This study aims to explore the existence of diverse religious groups in the province of Aceh and how they engage in religious activities alongside other groups. In collecting data, the researcher used the library research method to gather references from books, journals, and academic research reports related to the topic, as well as the Netnography method to gather public information through relevant social media. The results show that there are several different religious groups in Aceh with varying views and expressions of their rituals in different regions. The Tastafi group, Jama'ah Tabligh, and the T. Raja Ubiet community group have different characteristics and expressions in their spiritual activities. On the other hand, the Wahabi group shows a far different view from the local spiritual practices, causing them to be isolated from other religious groups. This study reinforces the reality that although Aceh has implemented Islamic law as positive law, religious groups can still thrive and not hinder the emergence of various religious expressions in the community.